INFLUENCE OF SCREENING BLOCK SUPPORTING WAY ON THE BEHAVIOUR OF A SOLID PARTICLE ON AN OSCILLATING SURFACE - EMILIAN MOŞNEGUŢU; VALENTIN NEDEFF; NARCIS BÂRSAN; ALEXANDRA-DANA CHIŢIMUŞ; DRAGOŞ RUSU (Journal of Engineering Studies and Research)
This article shows a study aiming to identify the influence carried out by the supporting way of the working surface in the case of plane oscillating screening device, over the behavior of a solid particle. In order to achieve this, a theoretical study has been conducted by using a simulation program, Working Model 2D, within which two ways of supporting the screening block have been conceived: the working surface supported by tie-rods, and the surface suspended on tie-rods. Following the simulation, a series of physical parameters has been determined: the trajectory followed by the solid particle; the circuit of the solid particle during its movement on the working surface; the acceleration of the solid particle and the reaction force occurred between the solid particle and the working surface. Following the analysis of resulting values it may be noted that the best way to support the working surface, as far as the efficiency of mechanical separation is concerned, according to width and thickness of the solid particle, is obtained in the case where the working surface is supported by tie-rods, since the running time of the working surface is the highest and it is 4.12 seconds, value generating the high average moving speed; the particle’s rotation angle is from -2 rad to +4.8 rad, having as a result the amplest possible rotation.